Wave 2 Survey Methodology - Wooden, M; Watson, N (Melbourne Institute of Applied Economic and Social Research, 2004)
This paper details the survey methodology employed for Wave 2 of the Household, Income and Labour Dynamics in Australia (HILDA) Survey. Many of the fieldwork procedures for Wave 2 concord with those used in Wave 1 and are documented in Watson and Wooden (2002). Any modified fieldwork procedures are reported in this document along with the response rates for Wave 2. An example of a procedure that is unchanged from Wave 1 that is not reported below is the use of incentives – $50 for fully responding households and $20 for partially responding households.
HILDA Project Technical Paper Series
Keywords: Surveys and Survey Methodology -- Fieldwork; Surveys and Survey Methodology; Surveys and Survey Methodology -- Dataset cleaning and development; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Dataset cleaning and development; Fieldwork; Surveys and Survey Methodology